AKIBAT HUKUM PENETAPAN DISPENSASI PERKAWINAN ANAK DI BAWAH UMUR (Studi Kasus di Pengadilan Agama Pacitan) - Mulyadi, Wisono; Nugraheni, Anjar Sri Ciptorukmi (Jurnal Privat Law, 2017)
AbstractThis article described and studied the following problems: firstly what is the Judge of Pacitan Religion Court’s rationale in granting or refusing the application for marriage dispensation?. Secondly, what is the legal consequence of the grant or the refusal of the application for marriage dispensation?. This study was an empirical or sociological research that was descriptive in nature. The types of data used were primary and secondary ones including primary, secondary and tertiary law materials. Techniques of collecting data used were field study and library study; and the technique of analyzing data used was the qualitative one with interactive model of analysis. The result of research showed that the Pacitan Religion Court’s rationale in granting or refusing an application for marriage dispensation was based on the evidences filed by the applicant. When the evidence filed was adequate and completed according to the Court and there was no kinship or sibling relationship and no prohibition to conduct marriage, the Chamber of Judge would have no reason to refuse the application. However, when the application was filed by non-authorized one, the evidence was inadequate, and there was a prohibition to conduct marriage, the application would be refused by the Chamber of Judge in Pacitan Religion Court. When the application for marriagedispensation was granted, the Pacitan Religion Court would release a stipulation mentioning that the marriage could be held. And then the applicant would bring the stipulation to the local Religion Affairs Office (KUA). Based on such the stipulation, KUA could hold the marriage of applicants. Meanwhile, when the application for marriage dispensation was refused, there would be no reason to get married until the marriage age was fulfilled by the applicants.Keywords: Marriage dispensation, Pacitan Religion Court, Marriage Law, Stipulation of the JudgeAbstrakArtikel  ini  mendiskripsikan  dan  mengkaji  permasalahan,  pertama  bagaimana  pertimbangan  Hakim Pengadilan Agama Pacitan dalam mengabulkan atau menolak permohonan dispensasi perkawinan. Kedua,  apa  akibat  hukum  yang  timbul  atas  dikabulkan  atau  ditolaknya  permohonan  dispensasi perkawinan. Penelitian ini adalah penelitian hukum empiris atau sosiologis bersifat deskriptif. Jenis data primer dan sekunder yang meliputi bahan hukum primer, sekunder, dan tersier. Teknik pengumpulan data yang digunakan adalah studi lapangan dan studi kepustakaan, selanjutnya teknis analisis yang digunakan adalah metode kualitatif dengan model analisis interaktif. Hasil penelitian menunjukkan bahwa Pertimbangan Hakim Pengadilan Agama Pacitan dalam mengabulkan atau menolak suatu permohonan dispensasi perkawinan didasarkan pada bukti-bukti yang diajukan oleh pemohon. Apabila bukti yang diajukan  sudah  cukup  dan  lengkap  menurut  Pengadilan,  serta  tidak  ada  hubungan  kekeluargaan maupun sesusuan, serta tidak ada larangan untuk melangsungkan perkawinan, maka Majelis Hakim tidak ada alasan untuk menolak permohonan. Akan tetapi, ketika permohonan diajukan bukan oleh orang yang berwenang, tidak terdapat bukti yang cukup, serta adanya larangan untuk melangsungkan perkawinan, maka permohonan akan ditolak oleh Majelis Hakim Pengadilan Agama Pacitan. Apabila permohonan dispensasi perkawinan dikabulkan, maka Pengadilan Agama Pacitan akan mengeluarkan sebuah penetapan yang berisi bahwa perkawinan dapat dilaksanakan. Kemudian Penetapan tersebut dibawa oleh pemohon ke Kantor Urusan Agama setempat. Berdasarkan penetapan tersebut, KUA dapat melaksanakan perkawinan pemohon. Sedangkan apabila permohonan dispensasi perkawinan ditolak maka tidak ada alas hak untuk menikah, hingga usia perkawinan terpenuhi oleh pemohon.Kata Kunci: Dispensasi Perkawinan, Pengadilan Agama Pacitan, Hukum Perkawinan, Penetapan Hakim